Argentinean copper concentrates: structural aspects and thermal behaviour - Bazan Brizuela, Vanesa Lucia (2013)
In Argentina, there are many sources of copper concentrates. Some of them are currently in operation, while others are in the exploration stage. All copper concentrates produced are exported to other countries for copper refinement and to create various finished products. It is desirable that in the near future, these copper concentrates be processed in an Argentinean industrial plant. The aim of this paper was to present the results of a characterisation study carried out on five different copper concentrate samples. The thermal decomposition of the copper concentrates was determined by differential thermal analysis and thermogravimetry (DTA TG). The information was correlated with the chemical composition and the mineralogical phases of the samples identified by X-ray diffraction. A melting test at temperatures of up to 1300˚C was performed to complete the study of the concentrate’s behaviour during heating. After the test, all of the samples were observed by light and electronic scanning microscopy to identify the different phases generated under high-temperature conditions.